Nordic hamstring strength of highly trained youth football players and its relation to sprint performance - Markovic, G.; Sarabon, N.; Boban, F.; Zoric, I.; Jelcic, M.; Sos, K.; Scappaticci, M. (The Journal of Strength and Conditioning Research, 2020)
We aimed to characterize Nordic hamstring (NH) strength and bilateral NH strength asymmetry in highly trained youth footballers and to investigate the relationship between NH strength and sprint performance. Twenty-two adult and 133 highly trained youth footballers in the age groups U12-U18 participated in this study. Eccentric hamstring strength was assessed using the NH device. Youth footballers (n = 119) also performed 20-m sprint test. Age-related changes in absolute and relative NH strength, and bilateral NH strength asymmetry were analyzed using 1-way analysis of variance. The linear relationship between relative NH strength and sprint performance was established using a Pearson correlation analysis. Significant age-related increases (F = 3.6-18.9; all p < 0.01) in NH strength were reported for all units except N·kg-1 (F = 1.9; p = 0.08). The largest differences in absolute NH strength were seen between U15 and U16 groups. Bilateral NH strength asymmetry varied from 8 to 16% (F = 1.8; p = 0.09) across all age groups. A large correlation between NH strength and sprint performance was observed (r = -0.52; p < 0.01). Our results indicate that NH strength increases nonlinearly with players' age, with the highest values observed in U16 group. Furthermore, bilateral NH strength asymmetry varied nonsignificantly between 8 and 16%. Finally, 27% of variance of sprint performance of youth footballers could be explained by relative NH strength. The reported NH strength data could be used as normative standards during testing and training of youth football players. Present results also suggest that coaches should pay close attention to eccentric hamstring function in youth footballers.